The ROV manual : a user guide for remotely operated vehicles - Christ, Robert D. (Elsevier, 2014)
Many underwater operations that were once carried out by divers can now be carried out more efficiently and safely with ROVs. Their use has spread rapidly too as the technology has become more efficient and affordable, with application now commonly seen in marine research and surveying, nuclear, hydroelectric and petroleum infrastructure inspection, harbor security and military contexts, among others. The ROV Manual is one of very few dedicated resources covering the use of ROVs, written by well-known experts in the field to provide a complete training and reference too.